SOCIO-PEDAGOGICAL AND PSYCHOLOGICAL FACTORS OF FORMATION OF STUDENT COMPETENCIES BASED ON THE REQUIREMENTS OF THE NATIONAL PROGRAM OF MOTHER TONGUE SCIENCE (Academia Science Repository, 2023)
In this article, human thinking, scientific potential, ability, socially important qualities are listed. In the future, our country will be prosperous and free, free and prosperous, and economically strong, in many ways depends on the ability and talent of today's youth to be deeply thoughtful, knowledgeable and spiritual. In the article, the importance of mother tongue education in the development of the young generation is great, and the importance of the mother tongue not only in mastering the same subjects, but also in the existence of a person in society, in the formation of communication in their interaction is mentioned.